Daya Predasi dan Tanggap Fungsional Kumbang Unta (Ophionea nigrofasciata) pada Beberapa Kepadatan Wereng Batang Coklat (Nilaparvata lugens) - Tre Julia Nasral; My Syahrawati; Yenny Liswarni (Plant Protection Departement, Faculty of Agriculture, Universitas Andalas, 2020)
Camel groundbeetle (Ophionea nigrofasciata Schmidt-Goble 1846) or CGB is reported as one of predators of brown planthopper (Nilaparvata lugens Stal 1854) or BPH. The difference in BPH densities is assumed to affect the predation rate of the CGB. This study aimed to determine the predation rate of CGB on BPH at different densities. This experiment used a completely randomized design (CRD) consisting of six treatments and five replications. The treatment consisted of predation of one CGB at several BPH densities (5, 10, 20, 30, 40, and 50 individuals). BPH used was second-third instar of nymphs, and the CGB used was female. The results showed that the predation rate of CGB increased with increasing BPH density with functional response types classified as type I (Linear). The highest predation occurred at 50 density (23.6 individuals or 47.2% of BPH provided). The difference in density of BPH did not affect the bodyweight gain of CGB and tended to decrease due to different prey-seeking behavior. Keywords: Nillaparvata lugens, Ophionea nigrofasciata, predation, predator